An Algorithmic Approach to Minimally Invasive Management of Nontraumatic Chylothorax - Goity, Luis D.; Itkin, Maxim; Nadolski, Gregory (Seminars in Interventional Radiology, 2020)
Chylothorax is a rare condition characterized by lymph accumulation in the pleural space. When it occurs independent of trauma, it is even more rare and difficult to treat as identification of lymphatic leak is unpredictable. In addition, treatment of this condition with conventional lymphangiography and thoracic duct embolization may not result in positive outcomes. As such, the role of contrast-enhanced dynamic magnetic resonance lymphangiography to guide treatment is key to maximizing success with the advantage of localizing the site of lymphatic leak. Herein, we summarize etiologies of nontraumatic chylothorax, offer an updated treatment algorithm to stratify affected patients and determine appropriate treatment options, and review procedural techniques critical to efficient and effective treatment.
Keywords: thoracic duct; chylous; chylothorax; lymphatic; interventional radiology; pleural space